Rubber tapping system effect on the productivity of Hevea brasiliensis in the Colombian Middle Magdalena (2017)
Tapping systems with stimulation are used to minimize costs and improve latex yield. For this, tapping systems with different frequencies and with or without Ethrel® stimulation and fertilizer levels were evaluated in a 9-yearold crop of FX3864 of Hevea brasiliensis in Barrancabermeja, Santander. In this study, a split plot design with randomized complete blocks was used, where the tapping systems with different frequencies with or without stimulation were considered as the principal plot and the fertilization treatments with combined dosages of N, P and K were considered as the subplots. The dry rubber yield, bark consumption, tapping panel dryness incidence, dry rubber content and profitability were considered as response variables. The systems d/3 E and d/4 E obtained the highest yield (1,446 and 1,281 kg ha-1 yr-1, respectively), with significant differences with the systems d/3 S.E and d/5 E. For the fertilization treatments, there were no significant differences. Notwithstanding, the highest yields were obtained in the 40-40-40 kg ha-1 and 80-80-80 kg ha-1 of N, P and K balanced treatments. The higher foliar levels of N, P, K and Ca were founded in the d/4 E system. According to these results, the d/4 E tapping system is recommended to be the most profitable under different tapping yields, with less bark consumption (3.86 cm), longer life plantation (3.85 years) and less disease panel incidence.